Non-woven PGA/PVA fibrous mesh as an appropriate scaffold for chondrocyte proliferation - Rampichová, M; Koštáková, E; Filová, E; Prosecká, E; Plencner, M; Ocheretná, L; Lytvynets, A; Lukáš, D; Amler, E (Physiological research, 2010)
Non-woven textile mesh from polyglycolic acid (PGA) was found as a proper material for chondrocyte adhesion but worse for their proliferation. Neither hyaluronic acid nor chitosan nor polyvinyl alcohol (PVA) increased chondrocyte adhesion. However, chondrocyte proliferation suffered from acidic byproducts of PGA degradation. However, the addition of PVA and/or chitosan into a wet-laid non-woven textile mesh from PGA improved chondrocyte proliferation seeded in vitro on the PGA-based composite scaffold namely due to a diminished acidification of their microenvironment. This PVA/PGA composite mesh used in combination with a proper hydrogel minimized the negative effect of PGA degradation without dropping positive parameters of the PGA wet-laid non-woven textile mesh. In fact, presence of PVA and/or chitosan in the PGA-based wet-laid non-woven textile mesh even advanced the PGA-based wet-laid non-woven textile mesh for chondrocyte seeding and artificial cartilage production due to a positive effect of PVA in such a scaffold on chondrocyte proliferation.
Keywords: textilie; Hyaluronic Acid; konfokální mikroskopie; chrupavka; Chondrocytes; Polyvinyl Alcohol; voda; Tissue Culture Techniques; buněčné dělení; techniky tkáňových kultur; králíci; buněčná adheze; Microscopy, Confocal; polyvinylalkohol; Animals; Textiles; chondrocyty; PEG-DMA hydrogel; Cell Division; zvířata; Hydrogel, Polyethylene Glycol Dimethacrylate; Tissue Scaffolds; Rabbits; Cartilage; tkáňové podpůrné struktury; Polyglycolic Acid; kyselina polyglykolová; kyselina hyaluronová; Water; Cell Adhesion